Investigating Conceptual Changes and Difficulties in Learning Mathematics during the Transitional Phase from Arithmetic to Algebra - Chaurasia, Dr. Prateek (Voices of Teachers and Teacher Educators, 2021)
The sequential nature of mathematics is well known, and prior knowledge makes it more prominent in the process of mathematical learning, especially in the phase when mathematics shifts from the basic concepts of arithmetic to algebra. While learning mathematics students start with the basic concepts of arithmetic and them proceed to further mathematical learning. Thus, these all are dependent on each other in a sequential pattern. This study tries to identify the main difficulties faced by students in this particular phase along with the intent to explore the transitional phase of mathematics. The present study was conducted with the aim to identify the difficulties faced by students in the learning of algebra. The study has also tried to identify its causes with the help of a process-based approach.